Padronização de técnica histoquímica de mensuração de lipídios da epiderme de cães e mensuração de lipídios da epiderme de cães atópicos antes e após reposição tópica de lipídios e ceramidas - Salvador, Marcela Cazagrande [UNESP] (2014)
Canine atopic dermatitis is a multifactorial skin disease with genetic origin, that causes itching as the main symptom. One of the disease's main characteristics (and a major causative factor) is the impairment of the epidermal skin barrier. This is caused, primarily, by a deficiency in the quantity of lipids in the epidermis of atopic dogs. However, no standardized histochemical technique for the evaluation of epidermal lipids in dogs exists in the literature. The objectives of this study were firstly, to standardize the measurement of lipids of the epidermis of normal dogs using specific histochemical staining. Secondly, using this standardized staining technique, ascertain the amount of epidermal lipids in atopic patients before and after treatment with topical replacement of lipids and compare with measurements from healthy dogs. For standardization of staining, epidermal samples from 25 healthy animals were taken and subjected to hematoxylin and eosin, Sudan Red and Oil Red O staining. The samples were processed using visual semi-quantitative assessment and by the digital image analysis program. After standardization, we compared the quantity of lipids in the epidermal barrier of 15 atopic dogs and 30 healthy dogs. Samples were taken from neck and axillae in all participating animals to assess any differences in lipid content between body regions. The results showed that Sudan Red provides the most accurate measurement of skin barrier lipids when comparing the lipid layer of the epidermis of healthy dogs with atopic dogs. It was found that atopic dogs exhibit a reduced quantity of lipids in the epidermal barrier prior to treatment and show a significant increase after topical replacement of lipids. Comparisons between individuals within the atopic group of animals showed that lipids from the neck occurred in smaller quantities than the axillary region. These results show that topical replacement of lipids in dogs with ...